Central core of uprolides D and E: a survey of some ring closing metathesis approaches - Ramana, C. V.; Salian, Sumanth R.; Gurjar, Mukund K. (Tetrahedron Letter, 2007)
A preliminary study dealing with the feasibility of ring closing metathesis and ene-yne ring closing metathesis to construct the central bicyclic cores of uprolides D and E was investigated. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: cembranolides; ene-yne metathesis; Ring closing metathesis; Sharpless asymmetric epoxidation; uprolides D and E

Expeditious assembly of 3,4-benzannulated 8-oxabicyclo[3.2.1]octane systems by [2+2+2] alkyne cyclotrimerisation: Total synthesis of (-)-bruguierol A - Ramana, Chepuri V.; Salian, Sumanth R.; Gonnade, Rajesh G. (European Journal of Organic Chemistry, 2007)
Facile construction of benzene-fused 8-oxabicyclo[3.2.1]octane systems by employing a cross alkyne cyclotrimerisation reaction was explored. With this procedure, (-)-bruguierol A was synthesised, and its absolute configuration was established.
Keywords: cyclotrimerisation; epoxidation; Total synthesis; Wilkinson's catalyst